Water footprints of energy sources in China: Exploring options to improve water efficiency. (10th February 2018) - Ding, Ning; Liu, Jingru; Yang, Jianxin; Lu, Bin
Abstract: Knowledge of water resource consumption and pollution during the life cycle of energy production and developing energy industry in regions with abundant water resources are two ways to improve water efficiency. In this study, a water footprint model for energy sources was developed, and water footprint inventories of the primary fossil fuels (e.g., coal, crude oil, natural gas) and power sources (e.g., thermal, nuclear, wind, solar photovoltaic, and hydropower) in China were compiled. The water footprints calculated for coal, crude oil, and natural gas were 0.14 m 3 /GJ, 0.29 m 3 /GJ, and 0.11 m 3 /GJ, respectively. The water footprints of power sources increased as follows: wind (0.14 m 3 /GJ), nuclear (0.19 m 3 /GJ), thermal (1.19 m 3 /GJ), solar (5.3 m 3 /GJ), and hydropower (6.75 m 3 /GJ). From a life cycle perspective, the water footprints of the three primary energy sources mainly originated from the extraction stages. The water footprint from upstream stages accounted for the highest proportion of the total water footprint of nuclear, wind, and solar power. Regional analyses revealed that provinces such as Sichuan, Yunnan, Hunan etc. have appropriate water resources and capacity for future development of energy system. A water footprint inventory of primary energy could provide basic data for water footprint analyses of secondary energy, materials, and products downstream across multiple sectors and could support water management in the energy industry.